Upcycling of spent LiCoO2 cathodes via nickel‐ and manganese‐doping. Issue 1 (15th June 2022) - Zhang, Nianji; Deng, Wenjing; Xu, Zhixiao; Wang, Xiaolei
Abstract: Direct recycling has been regarded as one of the most promising approaches to dealing with the increasing amount of spent lithium‐ion batteries (LIBs). However, the current direct recycling method remains insufficient to regenerate outdated cathodes to meet current industry needs as it only aims at recovering the structure and composition of degraded cathodes. Herein, a nickel (Ni) and manganese (Mn) co‐doping strategy has been adopted to enhance LiCoO2 (LCO) cathode for next‐generation high‐performance LIBs through a conventional hydrothermal treatment combined with short annealing approach. Unlike direct recycling methods that make no changes to the chemical composition of cathodes, the unique upcycling process fabricates a series of cathodes doped with different contents of Ni and Mn. The regenerated LCO cathode with 5% doping delivers excellent electrochemical performance with a discharge capacity of 160.23 mAh g −1 at 1.0 C and capacity retention of 91.2% after 100 cycles, considerably surpassing those of the pristine one (124.05 mAh g −1 and 89.05%). All results indicate the feasibility of such Ni–Mn co‐doping‐enabled upcycling on regenerating LCO cathodes. Abstract : Ni–Mn co‐doping is introduced to upcycle spent LiCoO2 (LCO) material through an improved hydrothermal treatment coupled with short annealing approach. The 5% Ni–Mn co‐doped material outperforms the pristine LCO material with an initial specific capacity of 160 mAh g −1 under a cut‐off potential of 4.35 V and 91% capacity retention after 100 cycles.